THE ROLE OF 3D PRINTING IN ENHANCING PROSTHODONTICS TREATMENT OUTCOMES; A SYSTEMATIC REVIEW (CAHIERS MAGELLANES-NS, 2025)
Everyone who has dealt with dental treatment in the past is aware of the fact that 3D printing has recently become a revolution especially in Prosthodontics. This systematic review aims at reviewing current use, advantage, and limitation of 3D printing in Prosthodontics. For this analysis, MEDLINE/Pub Med, SCI & Scopus, Web of science and Cochrane library databases were considered for article search. A rapid literature review was conducted for papers published from January 2000 to June 2024 as it was when 3D printing started to come to practice in dental field. Reviewing numerous studies and clinical cases, the authors emphasize that the application of 3D printing in dentistry leads to the increase of accuracy and customization, efficiency and, as a result, patients’ satisfaction. However, the technology is not without its limitations; it has the following drawbacks; material constraints; it is relatively expensive; and requires standardization of protocols. Exploring avenues for future research and practice (in applying 3D printing for dental treatment) are highlighted.